Pre-closure assessment of elevated arsenic and other potential environmental constraints to developing aquaculture and fisheries: The case of the Mae Moh mine and power plant, Lampang, Thailand. (April 2021) - Woon, S.H.J.; Srinuansom, K.; Chuah, C.J.; Ramchunder, Sorain J.; Promya, J.; Ziegler, A.D.
Abstract: Our assessment of 30 water bodies in the vicinity of the Mae Moh coal mine and power station in northern Thailand does not indicate substantial water quality management challenges to developing fisheries/aquaculture in peripheral reservoirs and streams. Negative water quality issues such as high concentrations of arsenic (2-17 μg/L) and ions including sulfate (868–2605 mg/L), sodium (217–552 mg/L), and total ammonia (<1–5 mg/L) were associated with groundwater and surface water resources on the facility, as well as the stream network draining from it. Total dissolved solids were also very high, ranging from 658 to 3610 mg/L. Six of seven ponds tested had As concentrations in the range of 5–17 μg/L. Although these levels are less than the Thai regulation for industrial effluent, they are elevated over background surface water concentrations. The highest concentration in a contaminated stream was 10.54 μg/L As, which is only slightly above the WHO (2017) regulation of 10 μg/L for drinking water. Ponds, contaminated streams, and deep subsurface water should not be used for fisheries/aquaculture without extensive remediation/treatment. Concentrations of these water parameters in peripheral streams and reservoirs were not of environmental concern. High water hardness (161–397 mg/L CaCO3 and potential ionic imbalances may be the greatest hindrances to developing sustainable fisheries and aquaculture in reservoirs in the study area. Routine monitoring of inorganic As species and other contaminants in water is needed to assess the full extent of arsenic risk at the site following closure. Graphical abstract: Image 1 Highlights: Arsenic, sodium, sulfate, and total ammonia concentrations are elevated in mine/plant waters. Water quality in the stream network below the facility is degraded. Water in peripheral streams and reservoirs are not contaminated by anthropogenic activity. Water hardness and ion imbalances may be problematic for fishery/aquaculture development.